The hope and horror of physicalism : an existential treatise - Brown, Christopher Devlin (New York, NY : Routledge, 2024)
"This book assesses the existentially relevant consequences of physicalism. It argues that accepting physicalism is the healthiest stance we can take in the face of an account of the self and world which offers no metaphysical assurances. Why should we care about physicalism? On one hand, the view seems to be inconsistent with things that many people find valuable, such as the existence of free will, God, the immortal soul, ultimate purpose, and natural laws like karma. On the other hand, physicalism seems to have positive existential implications, such as supporting the unlimited potential of scientific understanding or the attitude that we need not fear supernatural powers or forces because they don't exist. This book argues that physicalism has several consequences that are of existential import. It begins by outlining the history of physicalism and explaining two popular ways of understanding it: the via negativa approach and the theory-based approach. The rest of Part 1 explores the existential consequences of these two versions of physicalism. Part 2 draws on Nietzsche to construct an argument about what attitude we ought to adopt toward physicalism. It argues that we ought to avoid nihilism and despair even when confronted with a picture of the universe which offers no metaphysical assurances. Finally, Part 3 is dedicated to how well physicalism deals with the hard problem of consciousness, mental causation, and multiple realization. The Hope and Horror of Physicalism will appeal to anyone interested in a contemporary approach to existential philosophy, as well as scholars and advanced students working in philosophy of mind and metaphysics"--
Keywords: Logical positivism; PHILOSOPHY / Mind & Body; PHILOSOPHY / Movements / Existentialism